Arteriosclerosis of the abdominal aorta experimental production by the hemodynamic mechanism - Palma, E C; Passano de Moizo, M; Perillo, W; Fernández, E; Rodríguez Martínez, R J; Pedemonte, O.; González Viera, P (Cirugía del Uruguay, 2020)
Presented at session 5th August 1962